AKTIVITAS ANTIOKSIDAN MINUMAN FUNGSIONAL BERBASIS NIRA KELAPA DENGAN PENAMBAHAN EKSTRAK SECANG, KAYU MANIS, JAHE DAN BERAS HITAM - Ramadhan, Gumintang Ratna; Subardjo, Yovita Puri; Dwiyanti, Hidayah (Jurnal Gizi dan Pangan Soedirman, 2022)
The development of coconut sap-based products with the addition of secang wood extract, cinnamon, ginger and black rice is one of the right steps to provide a beverage source of antioxidants to suppress the development of degenerative diseases caused by exposure to free radicals. Objective: to examine the effect of the type and amount of extract on the total phenol, anthocyanin, antioxidant activity levels of coconut sap based- functional drinks by added extract of sappan wood, cinnamon, ginger and black rice based. This is a factorial experimental study using a Randomized Block Design. Factors tried were: 1) Type of extract (sappan wood (J1), cinnamon (J2), ginger (J3) and black rice (J4)); 2) amount of extract addition (15%, 20%, 25%). Variables observed were: total phenol and anthocyanin levels. The results showed that the type of extract and the amount of its addition affected on the total phenol and anthocyanin levels of functional beverages made from coconut sap. Functional beverages with the addition of sappan wood, cinnamon, ginger and black rice extracts contained total phenols of: (4.8; 3.68, 2.68 and 3.68)mg/mL and anthocyanins content of (25.23; 7,72; 8.76; and 38.22)mg/L, respectively.. The more the addition of extract, the higher the anthocyanin and phenol levels. The mean value of anthocyanin levels in the addition of extracts 15%, 20% and 25% were: (13.08; 18.81; and 28.05) mg/L and the total phenol content, (2.94; 3.59, and 4.21 GAE/g), and antioxidant actifity (DPPH) were: (65,3%), (66,7%), (69% ) respectively. Functional drink based on coconut sap with the addition of black rice extract has the highest antioxidant activity.Keyword : secang wood, cinnamon, ginger, black rice